Prognostic significance of tumor laterality in advanced ovarian cancer - Yuki Yamada; Seiji Mabuchi; Naoki Kawahara; Ryuji Kawaguchi (Korean Society of Obstetrics and Gynecology, 2021)
Objective This study aimed to investigate the effect of incorporating tumor laterality into the International Federation of Gynecology and Obstetrics (FIGO) staging system for advanced ovarian cancer. Methods The clinical data of 131 patients with advanced ovarian cancer treated between 2008 and 2018 were retrospectively reviewed. To investigate the prognostic significance of tumor laterality, we divided the patients into unilateral and bilateral groups. The prognostic significance of tumor laterality (bilateral vs. unilateral) was evaluated using univariate and multivariate analyses. The effect of incorporating tumor laterality into the FIGO staging system to predict survival outcomes was evaluated using the Kaplan-Meier method. Results Both overall survival (OS) and progression-free survival (PFS) were longer in the unilateral group than in the bilateral group. Multivariate analysis demonstrated that tumor laterality was an independent predictor of OS (hazard ratio, 1.75; confidence interval, 1.05-2.92; P=0.032). In patients with stage III disease, the bilateral group had a shorter OS than the unilateral group, but it was comparable to the OS in stage IV patients (P=0.354). The incorporation of tumor laterality into the FIGO staging system improved the stratification of survival probabilities. Conclusion Tumor laterality can be an independent prognostic factor in patients with advanced ovarian cancer. The incorporation of tumor laterality may improve the predictive performance of the FIGO staging system in patients with advanced ovarian cancer.